Law Enforcement of Paper Rupiah Mutilation Practice from the Perspective of Law Number 7 of 2011 Concerning Currency and Jarimah Ta’zir - Al Munawar, Faishal Agil; Wiria Tarita, Yuanggi Nur (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
The practice of mutilating paper currency notes is very dangerous. This practice not only damages the currency, but also attempts to counterfeit it. The emergence of this practice not only shakes economic stability, but also reflects the weakness of law enforcement. Law enforcement against this practice is still relatively weak. This research is an empirical juridical legal research with a legal sociology approach. Data sources consist of primary data and secondary data. The data collection method uses direct interviews, documentation, and literature study. The purpose of the research is to find out the law enforcement on the practice of mutilation of paper rupiah bills carried out by the Representative Office of Bank Indonesia Malang, as well as a review of the Currency Law and Islamic law, namely jarimah ta’zir. The results showed that the Representative Office of Bank Indonesia Malang is always proactive and aggressively conducts education, socialization, appeals, and cooperates with other law enforcement agencies. This practice according to Law Number 7 of 2011 concerning Currency has violated several articles, namely Article 25 Paragraph 1, Article 26 Paragraph 1, Article 35 Paragraph 1, Article 36 Paragraph 1, Article 38 paragraphs 1 and 2, Article 40 Paragraph 1, and Article 41 Paragraph 2 and if according to jarimah ta’zir, the Indonesian government applies ta’zir punishment in the form of imprisonment, fines, and additional punishment of revocation of business licenses or deprivation of certain goods.